ANALYSIS AND EVALUATION OF OFFICE INDOOR AIR QUALITY IN SURABAYA CITY - Moch Sahri; Octavianus Hutapea (Universitas Darussalam Gontor, 2019)
AbstractOffice is a place for a group of people to carry out administrative activities. The office was formed with the aim of providing good and controlled communication and recording services for information. Office activities generally consist of activities related to office planning, office organizing, office direction, and office supervision. Seeing the complex types of activities in the office, of course, there are activities and use of office equipment that can affect the air quality in the room. The problem of indoor air quality is recognized as an important risk factor for health because the working community spends most of its time in the building or work space. Decreasing air quality in space can cause health problems for residents or commonly called sick building syndrome.The purpose of this study in general is to determine the air quality of the room which includes physical factors and chemical factors and compare with the standard values based on the regulation of the ministry of health of the Republic of Indonesia number 48 of 2016 concerning office health and safety.The object in this study is one of the offices in the city of Surabaya. The position of this office location is located in the middle of Surabaya. The number of rooms measured in this research is 11 rooms.Based on the results of measurements of physical factors in the office space, the results of noise measurements still meet the standards, there are 9 rooms that do not meet the lighting standards, there are 5 rooms that do not meet room temperature standards and there are 7 rooms that do not meet humidity standards. the results of testing the chemical factors for the parameters CO, CO2, O2 and Ozone still meet the standards, HCOH parameters there are 3 locations that do not meet the standards and parameters of dust, there can be 4 rooms that do not meet the standards. Keywords: evaluation; indoor air qualty; office room.